QUIZZES THAT PROMOTE MOTIVATION IN LEARNING - Merilyn Simbolon; Nina Nina; Nurfitrini Ramadhani (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2019)
This research deals with how quizzes promote the students’ motivation in learning. There are two types of motivation in learning namely intrinsic motivation and extrinsic motivation. Intrinsic motivation refers to doing something because it is inherently interesting or enjoyable, and extrinsic motivation refers to doing something because it leads to a separable outcome. Quizzes are formative assessment to measure the ongoing teaching and learning. This research is a descriptive under qualitative research which was conducted in SMP Katolik Santa Maria Palangka Raya. It was taking all the English teachers and three classes of students chosen randomly (there would be one class to represent each grade) as participants. The questionnaires were applied to all of participant students to find out how the quizzes promote their motivation in learning and to all of the English teacher to support the findings on students’ responses. It finds out that quizzes are (1) challenging, (2) checking their understanding, (3) having various types, (4) practicing the teamwork, (5) providing feedback, (6) improving their learning and (7) practicing their competition. So, quizzes simply involve the instruments of the two types of motivation; intrinsic and extrinsic motivation.